2012
DOI: 10.3892/or.2012.2127
|View full text |Cite
|
Sign up to set email alerts
|

Casticin, a flavonoid, potentiates TRAIL-induced apoptosis through modulation of anti-apoptotic proteins and death receptor 5 in colon cancer cells

Abstract: We investigated the effect of casticin on apoptosis induced by tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL). We found that casticin potentiated TRAIL-induced apoptosis in human colon cancer cells. Casticin downregulated cell survival proteins including Bcl-xL, Bcl-2, survivin, XIAP and cFLIP, and induced death receptor 5 (DR5), but had no effect on DR4 and decoy receptors (DcR1 or DcR2). Deletion of DR5 by siRNA significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Oxidative stress by chemopreventive agents, including curcumin and casticin, has been implicated in DR5 upregulation and apoptosis (35)(36)(37). Furthermore, numerous natural antitumor compounds have been reported to induce ROS production (35,37).…”
Section: Ros Is Involved In Andrographolide-induced Sensitization To mentioning
confidence: 99%
“…Oxidative stress by chemopreventive agents, including curcumin and casticin, has been implicated in DR5 upregulation and apoptosis (35)(36)(37). Furthermore, numerous natural antitumor compounds have been reported to induce ROS production (35,37).…”
Section: Ros Is Involved In Andrographolide-induced Sensitization To mentioning
confidence: 99%
“…It has been identified that the C-3 and C-4' methoxy and C-3' and C-5 hydroxy functional groups provide the strong anti-proliferative activity of this flavonoid (18). Casticin exhibits weaker cytotoxicity but greater selectivity than taxol, (the IC 50 of taxol for tumor cells is at the nmol/l level, while the IC 50 of casticin is at the µmol/l level) (19).…”
Section: Introductionmentioning
confidence: 99%
“…They are derived from plants and were also found in insect tea. The flavones from different plants all showed strong apoptotic effects in cancer cells (Liu et al, 2014;Tang et al, 2013). In this study, insect tea had a strong apoptotic-inducing effect in HepG2 cancer cells.…”
Section: Chemical Constituents Of Insect Teamentioning
confidence: 77%